EXPLORING ERRORS AND MISTAKES IN THE STRUCTURE OF GRAMMAR AT UNIVERSITY LEVEL IN KHAIRPUR MIR’S SINDH - Sonal Khan Maitlo; Azhar Ahmad; Sajid Ali; Abdul Rehman Soomro (International Journal of Contemporary Issues in Social Sciences, 2023)
The main purpose of this research was to explore the errors and mistakes in grammar in English assignments of undergraduates in district Khairpur Mir’s Sindh. The researchers used quantitative approach for the present research and from the population of the study was the ESL students of a private university in district Khairpur. The researchers randomly selected twenty assignments of these ESL undergraduates level students for the purpose of exploring errors and mistakes in grammar, and find eleven types of grammatical errors and mistakes in these assignments. The results show that the most common errors and mistakes were in punctuations, spellings, prepositions and tense. Besides, some students also committed errors and mistakes in the use of adverb, subject verb agreement, pluralization, pronoun, conjunction, articles and adjectives. The results were analyzed in numerical form and presented in figures and graphs. In the end researchers give some guiding principles for ESL instructors and learners in correcting grammatical errors and mistakes in their academic writings. Moreover, the researches also suggested some recommendations for future researchers of this field.